Closing the execution gap how great leaders and their companies get results - Lepsinger, Richard 1948- (Jossey-Bass, 2010)
Why can some companies get things done day-to-day and deliver consistent results? Based on an extensive research from more than 400 companies, this book outlines five baseline factors critical for effective execution and five factors that differentiate companies that are most effective at executing plans and initiatives. It also explores the seven specific things leaders at all levels can do to close the execution gap in their company or team and help people get things done day-to-day. This is an essential guide for consistently executing effective plans and initiatives.
Includes bibliographical references and index. - Print version record
Keywords: Organizational effectiveness; Performance; Leadership; Management; Performance technology; Efficacité organisationnelle; Rendement au travail; Gestion; management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management